Fungal diseases: could nanostructured drug delivery systems be a novel paradigm for therapy? - Voltan, Aline Raquel [UNESP]; Quindos, Guillermo; Medina Alarcon, Kaila P. [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Soares Mendes-Giannini, Maria Jose [UNESP]; Chorilli, Marlus [UNESP] (Dove Medical Press Ltd, 2016)
Invasive mycoses are a major problem for immunocompromised individuals and patients in intensive care units. Morbidity and mortality rates of these infections are high because of late diagnosis and delayed treatment. Moreover, the number of available antifungal agents is low, and there are problems with toxicity and resistance. Alternatives for treating invasive fungal infections are necessary. Nanostructured systems could be excellent carriers for antifungal drugs, reducing toxicity and targeting their action. The use of nanostructured systems for antifungal therapy began in the 1990s, with the appearance of lipid formulations of amphotericin B. This review encompasses different antifungal drug delivery systems, such as liposomes, carriers based on solid lipids and nanostructure lipids, polymeric nanoparticles, dendrimers, and others. All these delivery systems have advantages and disadvantages. Main advantages are the improvement in the antifungal properties, such as bioavailability, reduction in toxicity, and target tissue, which facilitates innovative therapeutic techniques. Conversely, a major disadvantage is the high cost of production. In the near future, the use of nanosystems for drug delivery strategies can be used for delivering peptides, including mucoadhesive systems for the treatment of oral and vaginal candidiasis.
Keywords: fungal diseases; antifungal agents; amphotericin B; azoles; nanoparticles; nanotechnology